2009
DOI: 10.3152/030234209x461006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of research funding and science policy on university research performance: a comparison of five countries

Abstract: The ability of universities to efficiently produce high-standard knowledge has become an important goal in science policies of many developed countries. Thus, many countries nowadays steer universities based on performance monitoring and competition. This article analyzes the connection between the competitiveness of the university funding environment and research performance in five OECD countries in 1987-2006. Besides funding, other science policy factors are analyzed using the framework of four state steeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 10 publications
0
20
0
2
Order By: Relevance
“…As we noted in the literature, the new accountability was not successful in the US context (e.g., Shin and Milton 2004;Volkwein and Tandberg 2008). Comparative studies also found that the new accountability did not contribute to institutional performance (e.g., Huisman and Currie 2004;Himanen et al 2009). For example, in their recent comparative study of five countries (Australia, Finland, the Netherlands, Norway, and the UK) Himanen and associates (2009) found that the performance-based funding policy did not contribute to research productivity.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As we noted in the literature, the new accountability was not successful in the US context (e.g., Shin and Milton 2004;Volkwein and Tandberg 2008). Comparative studies also found that the new accountability did not contribute to institutional performance (e.g., Huisman and Currie 2004;Himanen et al 2009). For example, in their recent comparative study of five countries (Australia, Finland, the Netherlands, Norway, and the UK) Himanen and associates (2009) found that the performance-based funding policy did not contribute to research productivity.…”
Section: Discussionmentioning
confidence: 81%
“…The emergence of the new accountability had both historical and theoretical bases. For instance, higher education scholars have long argued that higher education institutions will enhance institutional performance if they are autonomous (e.g., Carnegie Foundation for the Advancement of Teaching 1982;Clark 1983;Himanen et al 2009;Volkwein 1987). Policymakers began to lessen regulations and empower campus leaders in the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the indications of Liu (2003) and Jongbloed (2008), policy-makers have to take either an ''input-oriented'' approach if the budgets are driven by the demography of an institution, an ''output-oriented'' approach if the budgets are tied to specific research outcomes of the institutions' activities, or both approaches in funding the defined intervention. To our knowledge, some studies regard input criterion as more commonly used (Kaiser et al 2001;Miroiu and Aligica 2003), whereas others believe that funding on the basis of output has increased because it contains more incentives for efficient behavior (Liu 2003;Jongbloed 2008;Himanen et al 2009). This discrepancy encourages us to ask whether government or industry funding is driven by university demography, benefits derived from innovation performance, or both?…”
Section: The Causal-effect Of Funding Allocationmentioning
confidence: 97%
“…However, the input criterion is dominant. The funding mechanism of Taiwan is still under development and is to be improved since the effects of increase output-orientation on several developed countries can be seen (Jongbloed 2008;Himanen et al 2009). Corresponding to the second question, we conclude that in addition to demography or innovation performance, industry funding is also stimulated by the amount of government funding.…”
Section: Conclusion and Further Studiesmentioning
confidence: 98%
“…A second research perspective targets the implementation and implications of performance-based funding systems for research work (Geuna and Martin 2003;Himanen et al 2009;Hicks 2012). In combination with research evaluation, performance-based funding made universities recognize the importance of research as a source of reputation and, more importantly, income (Whitley and Gläser 2007).…”
Section: Targeting Changes In the Funding Of Sciencementioning
confidence: 99%